2021
DOI: 10.3390/s21155071
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Commercial Wearable Technology: Contributions toward Accurate and Free-Living Monitoring of Sleep

Abstract: Despite prolific demands and sales, commercial sleep assessment is primarily limited by the inability to “measure” sleep itself; rather, secondary physiological signals are captured, combined, and subsequently classified as sleep or a specific sleep state. Using markedly different approaches compared with gold-standard polysomnography, wearable companies purporting to measure sleep have rapidly developed during recent decades. These devices are advertised to monitor sleep via sensors such as accelerometers, el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 99 publications
1
13
0
Order By: Relevance
“…Wearable sleep monitoring is gaining popularity, indicating the possibility of expanding burnout research through the use of wearable technology ( 58 ). On the other hand, the wide range of accuracy among commercial sleep technologies highlights the critical need for ongoing evaluations of newly developed sleep technologies ( 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wearable sleep monitoring is gaining popularity, indicating the possibility of expanding burnout research through the use of wearable technology ( 58 ). On the other hand, the wide range of accuracy among commercial sleep technologies highlights the critical need for ongoing evaluations of newly developed sleep technologies ( 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both PA and sleep are related to each other. Wearable technology is currently being used to track PA and sleep, which could help researchers study sleep science in-depth, resulting in the better diagnosis of sleep-related disorders [ 84 ]. Sathyanarayana et al demonstrated that deep learning can be used to predict sleep quality (whether it was good or poor) by making use of an actigraph obtained from the waking hours of an individual [ 85 ].…”
Section: Wearables As Digital Diagnosticsmentioning
confidence: 99%
“…To ensure an effective identification of the most crucial parameters, work should be put into developing user interfaces that offer users a variety of pertinent information and can be easily adopted without requiring programming knowledge and skills. There are some excellent review articles that have discussed the properties and sensing mechanism of commercially available wearable healthcare devices [ 20 , 21 , 22 , 23 ].…”
Section: Healthcare Wearablesmentioning
confidence: 99%